2021
DOI: 10.1021/acsestwater.1c00072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Hydrology on Plastic Transport in a Subtropical River

Abstract: Temporal and spatial variability are thought to drive river plastic transport, but most field data collections are limited to sporadic sampling at one location, constraining our ability to predict plastic pollution accurately. In this study, we assessed the impact of seasonal and longitudinal variability on river plastic loads collected during 18 months in Florida (USA). We used multipoint cross-sectional sampling, coupling a 500 μm Neuston net with an Acoustic Doppler Currency Profiler at three sites along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 99 publications
(236 reference statements)
2
16
0
Order By: Relevance
“…Various hydrometeorological variables have been correlated to the mobilization, transport, dispersion, and accumulation of plastics in rivers. Examples include wind (Bruge et al, 2018;Roebroek et al, 2021a), river flow velocity and discharge (Haberstroh et al, 2021), and precipitation-induced runoff (Treilles et al, 2021). Hydrology is not only important for mobilization and transport processes, but also determines when and where plastics accumulate in river systems (Liro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Various hydrometeorological variables have been correlated to the mobilization, transport, dispersion, and accumulation of plastics in rivers. Examples include wind (Bruge et al, 2018;Roebroek et al, 2021a), river flow velocity and discharge (Haberstroh et al, 2021), and precipitation-induced runoff (Treilles et al, 2021). Hydrology is not only important for mobilization and transport processes, but also determines when and where plastics accumulate in river systems (Liro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their low density, small fibres tend to occur rather close to the surface, which is reflected especially in our cascade samples. Numerous potential sources can contribute microplastics to the river, e.g., urban and industrial areas within the catchment in general and waste water treatment plants as typical effluents for fibres in particular (Kay et al, 2018;Haberstroh et al, 2021).…”
Section: Comparison With Other Parts Of the Elbe And European Riversmentioning
confidence: 99%
“…A comparison with rivers on a global scale remains challenging as well. Besides the complexity of fluvial dynamics, different climatic and geomorphological conditions, the occurrence and distribution of microplastics may vary strongly (Kay et al, 2018;Haberstroh et al, 2021). Nevertheless, several studies showed that rivers draining large, densely populated and industrialized catchments carry considerable loads of microplastics (Lebreton et al, 2017;Gerolin et al, 2020;Napper et al, 2021) and discharge an amount of approximately 1.15-2.41 million tonnes of (micro and macro) plastic per year into the world oceans (Lebreton et al, 2017).…”
Section: Comparison With Other Parts Of the Elbe And European Riversmentioning
confidence: 99%
See 2 more Smart Citations